Community Diagnosis: Kesadaran Pengelolaan Sampah Rumah Tangga Dusun Pagergunung 1 Bantul - Djannah, Siti Nur; Fitriani, Isah (DHARMA BAKTI, 2023)
Household waste management is a very urgent problem, because it can have an impact on polluting the environment and causing various diseases. It is hoped that the community must be more aware and care about being responsible for handling household waste properly. This service was carried out through 2 stages, namely community diagnosis using the 2018 RISKESDAS adoption questionnaire and health education. Based on the results of data analysis, it can be seen that burning waste is the main problem faced by residents of RT 04 Dusun Pagergunung 1 with a prevalence of 34%. Some people complain of coughing, environmental pollution, and the smell of smoke sticking to their clothes, so they feel disadvantaged. conducting counseling about the dangers of burning waste and managing housing and settlement health. Thus, it is hoped that the community will be willing and able to sort waste independently before disposing of it to TPS/TPA and apply the 5R principles (reduce, reuse, recycle, recovery and repair).